2016
DOI: 10.1038/srep37307
|View full text |Cite
|
Sign up to set email alerts
|

Statistical power considerations in genotype-based recall randomized controlled trials

Abstract: Randomized controlled trials (RCT) are often underpowered for validating gene-treatment interactions. Using published data from the Diabetes Prevention Program (DPP), we examined power in conventional and genotype-based recall (GBR) trials. We calculated sample size and statistical power for gene-metformin interactions (vs. placebo) using incidence rates, gene-drug interaction effect estimates and allele frequencies reported in the DPP for the rs8065082 SLC47A1 variant, a metformin transported encoding locus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Moreover, the design and implementation of new studies, such as genotype-based recall clinical trials intended for the investigation of genetic and lifestyle interactions, with more accurate objective measurement of diet are required to better understand the interplay between genetic and lifestyle factors on the risk of type 2 diabetes. 54 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the design and implementation of new studies, such as genotype-based recall clinical trials intended for the investigation of genetic and lifestyle interactions, with more accurate objective measurement of diet are required to better understand the interplay between genetic and lifestyle factors on the risk of type 2 diabetes. 54 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the careful integration of these more detailed exposure measures with multi-omics data (epigenomics, transcriptomics, proteomics metabolomics or metagenomics) [52 •• ], is likely to be necessary if we are to understand the complexities of gene × lifestyle interactions, and translate this knowledge into clinical action. Moreover, the application of cutting-edge technologies to biomaterials from historical cohorts, whilst powerful in many ways, requires the design and implementation of new studies, intended specifically for the investigation of gene × lifestyle interactions; such studies are likely to include genotype-based recall clinical trials [53].…”
Section: Future Key Challenges and Concluding Remarksmentioning
confidence: 99%
“…The vast majority of published GBR studies have focused on elucidating how genetic variants manifest phenotypically. Other forms of GBR have looked to assess the causal impact of specific risk factors and also to enhance trial design through informed participant selection 2, 3 . More than a dozen GBR studies focusing on cardiometabolic traits have been reported in the past two decades 420 with contrasting genetic characteristics, with the PPARG Pro12Ala variant (rs1801282) being the single most extensively studied locus.…”
Section: Overview Of Published Gbr Studiesmentioning
confidence: 99%